A Strategic Model for Enhancing Organizational Citizenship Behavior Through Transformational Leadership and Emotional Intelligence in Educational Institutions - Chandra, Khitara Aldilla; Yusnita, Nancy; Sunaryo, Widodo (Dinasti Publisher, 2026)
This study examines the suboptimal level of Organizational Citizenship Behavior (OCB) among educational support staff, indicated by low initiative, limited extra role involvement, and minimal contribution to organizational effectiveness. OCB represents voluntary behavior that enhances individual performance and supports the effectiveness and sustainability of educational organizations, particularly private vocational high schools in Bogor Regency. Strengthening OCB is essential to create a collaborative, adaptive, and service oriented work environment. This study aims to develop strategic efforts to enhance OCB by analyzing the direct and indirect effects of Transformational Leadership and Emotional Intelligence, with Job Satisfaction as an intervening variable. A quantitative survey approach was employed. The population consisted of educational support staff at private vocational high schools in Bogor Regency, with 186 respondents selected through proportional random sampling. Data were collected using validated and reliable questionnaires and analyzed using descriptive statistics, correlation analysis, and path analysis. The results show that Transformational Leadership and Emotional Intelligence have positive and significant direct effects on OCB. Job Satisfaction also has a positive and significant direct effect on OCB. Additionally, Transformational Leadership and Emotional Intelligence positively influence Job Satisfaction. Mediation analysis confirms that Job Satisfaction mediates the effects of Leadership and Emotional Intelligence on OCB.